2001
DOI: 10.1254/jjp.86.316
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of GABAergic Systems in Manifestation of Pharmacological Activity of Desipramine

Abstract: ABSTRACT-We have conducted this study to elucidate the influence of GABAergic systems on manifestation of pharmacological activity of desipramine using both pharmacological and electrophysiological methods. Desipramine (20 mg /kg, i.p.) significantly blocked the adjuvant-induced thermal hyperalgesia, which was facilitated by treatment with the GABAA antagonist picrotoxin (2 mg/ kg, i.p.) or the GABAB antagonist saclofen (2 mg/kg, i.p.). This analgesic effect of desipramine was antagonized by post-treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…1). The doses of the drugs used were chosen based on the literature review and preliminary pilot study [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…1). The doses of the drugs used were chosen based on the literature review and preliminary pilot study [23,24].…”
Section: Methodsmentioning
confidence: 99%
“…Desipramine has been shown to alter levels of many molecules in vivo and in vitro. Desipramine decreases tumour necrosis factor- production in the brain, 1 downregulates the cortical  1 -and  2adrenoceptors in rat brain, 2 inhibits cytochrome P450 enzymes, 3 inhibits the neuronal and skeletal ATP-Ca 2 pump of the endoplasmic reticulum, 4 inhibits the plasma membrane Ca 2 pump, 5 enhances the function of membrane steroid transporters, 6 activates GABAergic systems 7 and alters protein kinase C activity in rat brain and rabbit platelets. 8 The aim of the present study was to explore the effect of desipramine on apoptotic pathways in osteosarcoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…NMDA-activated ion current has also been shown to be inhibited by desipramine, imipramine and amitriptyline (White et al 1990;Watanabe et al 1993), although another study reported that desmethylimipramine potentiates NMDA responses (Lancaster and Davies 1991). The anti-nociceptive action of desipramine has been suggested to be mediated through the GABAergic system (Asahi and Yonehara 2001). Furthermore, TCAs have been shown to induce convulsive seizures which are due to inhibition of GABA A receptors (Malatynska et al 1988).…”
Section: Discussionmentioning
confidence: 99%